A Case Report of Cardiofaciocutaneous Syndrome with MAP2K1 Pathogenic Variant [Letter] - Furqoni AH; Fajarwati I; Poetranto AL (Pharmacogenomics and Personalized Medicine, 2023)
Abdul Hadi Furqoni, Indah Fajarwati, Anna Lystia Poetranto Center for Biomedical Research, Research Organization for Health, National Research and Innovation Agency (BRIN), Cibinong Science Center, Cibinong - Bogor, West Java, IndonesiaCorrespondence: Abdul Hadi Furqoni, Center for Biomedical Research, Research Organization for Health, National Research and Innovation Agency (BRIN), Cibinong Science Center, Jl. Raya Bogor No. 490, Cibinong – Bogor Km. 46, Cibinong - Bogor, West Java, 16911, Indonesia, Tel +6287850593847, Email cocohadi01@gmail.com